Trade-off between Outreach and Profitability in Microfinance Institutions: Evidence from Bangladesh - Aminudin Ma'ruf; Hamim Azad (Institut Agama Islam Negeri Madura, 2023)
Claims have been made that the purpose of microfinance is to alleviate poverty and remain sustainable. Hence, there is a trade-off between outreach to the low-income community and financial profitability. This research study tried to examine the trade-off between outreach and profitability of microfinance institutions in the context of Bangladesh. This study uses a data sample of 433 Microfinance Institutions obtained from the Microcredit Regulatory Authority on Microfinance Institutions in Bangladesh. Factors that significantly influence the outreach are the Total number of borrowers and Loan size to borrowers, while the profitability, is Equity to asset and Total assets. The result shows that there is significant evidence of a trade-off between outreach and profitability in Microfinance Institutions in Bangladesh. Furthermore, the paper recommends Microfinance Institutions remain small in order to maximize their outreach and urges policymakers to develop robust regulations on microfinance to help the poor community and support the nation’s economy for long-term prosperity.